2010
DOI: 10.2298/mpns1008527k
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral palsy and epilepsy

Abstract: The objective of the paper was to show the relationship between cerebral palsy and epilepsy and to determine the occurrence, associated factors, nature and prognosis of epilepsy in children with cerebral palsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
0
5
0
3
Order By: Relevance
“…The age of onset of epilepsy was frequently analyzed in various studies that have concluded that this is often under the age of one year, and that the earlier the onset of seizures is, the more severe forms of epilepsy will develop [8,20,21]. In our study we identified a high percentage of drug resistant forms of epilepsy (30.8%), nearly half of them (46.4%) being associated with quadriplegia.…”
Section: Discussionmentioning
confidence: 60%
“…The age of onset of epilepsy was frequently analyzed in various studies that have concluded that this is often under the age of one year, and that the earlier the onset of seizures is, the more severe forms of epilepsy will develop [8,20,21]. In our study we identified a high percentage of drug resistant forms of epilepsy (30.8%), nearly half of them (46.4%) being associated with quadriplegia.…”
Section: Discussionmentioning
confidence: 60%
“…It has been found that 15-60% of children with CP are affected with epilepsy [22]. Such patients suffer frequent attacks of epileptic seizures like generalized tonic clonic, myoclonic/ atonic, partial seizures and few of them also are victims of other epileptic associated syndromes viz infantile spasms, west and lennox-gastaut syndrome [23,24]. Though seizures can be controlled by pharmacotherapy, but epilepsy still remains an area of concern as epilepsy in patients with CP is of severe nature and difficult to control.…”
Section: Discussionmentioning
confidence: 99%
“…CP is also associated with a higher incidence of seizures. The most frequent seizure types are complex focal and secondary generalized seizures, for which an early evaluation is strongly recommended [ 2 ] as children with CP tend to have an earlier epilepsy onset, and the degree of severity is positively correlated with the CPs severity.…”
Section: Introductionmentioning
confidence: 99%
“…Intellectual disabilities constitute a unique difficulty for epilepsy in children with CP. Typically, these children cannot describe epileptic events, parents describe them with apprehension, and epilepsy specialists rarely witness them [ 2 ]. The clinical course is not well defined, although epilepsy occurs in up to 90% of children with CP [ 1 ].…”
Section: Introductionmentioning
confidence: 99%